Dating violence in adolescent forensic cases with history of sexual abuse - PERDAHLI FİŞ, NEŞE (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2016)
Objective: Dating violence defined as physical, sexual or psychological/emotional violence within a dating relationship. Consequences identified from longitudinal studies include cigarette smoking, marijuana and other illicit substance use, antisocial behavior, depression, and suicide ideation and attempts. We aimed to examine the concept of dating violence within a group of adolescent forensic sexual abuse cases. Methods: The files of girls aged 1218 years who had been referred to child psychiatry forensic outpatient clinic between September 2010 and December 2012 were examined retrospectively. The group with the presence of dating violence was compared to the group without dating violence with regard to characteristics of abuse and psychiatric findings from the clinical interview. Results: The mean age of our sample was 15.20 +/- 1.67 years. Almost 75% of the cases had been abused by someone they were familiar with. Among them dating partners were the first on the list. In both groups the most common psychiatric diagnoses were post traumatic stress disorder and acute stress disorder, followed by major depression. Those girls, who were subjected to dating violence, had significantly more suicidal acts after the trauma. Sexual abuse with penetration was significantly higher in the dating violence group. Conclusion: The term 'dating violence', has long been known in western countries and has been regarded as a serious public health problem. It is a relatively new term in our country. Due to its serious consequences, such as increased suicidal attempts, the awareness about dating violence should become an issue of great importance.
Keywords: sexual abuse; forensic cases; dating violence; RISK-FACTORS; CLINICAL-FEATURES; VICTIMIZATION; CHILDREN; HEALTH; ASSOCIATIONS; IMPACT; SAMPLE; RAPE